Surface Treatment of Epoxy/Al Composite by Dielectric Barrier Discharge (DBD) at Atmospheric Pressure - Abd, Aseel Kamel; Abbas, Qusay Adnan (Iraqi Journal of Science, 2023)
In this study, the surface of the epoxy/Al composite is treated using a dielectric barrier discharge (DBD) plasma in the presence of air. The epoxy composite was prepared by mixing 0.1g and 0.3 g aluminum powder with epoxy resin and its hardener in a ratio of 3:1. The surface epoxy/Al composite as a dielectric barrier layer (DB) is studied at an applied frequency of 8 kHz and at three exposure times 0, 2, and 4 min. The UV degradation process has been studied using UV-Visible spectroscopy, for these polymers. The absorbance intensity in the UV region (200–320 nm) was high. The absorbance level decreased after 2 minutes and increased after 4 min exposure time. Before exposure to plasma, the epoxy/Al composite at 0.1 g Al had an optical band gap of 3.72eV, while it was 3.6 and 3.42 eV after 2, and 4 min exposure time, respectively. For the composite with 0.3 g Al, the optical band gap was 3.6 eV before exposure which decreased to 3.2 and 2.78 eV after exposure to plasma for 2 and 4 min, respectively. This was due to the increase in conductivity for epoxy/Al composite with 0.3 g Al. Also, after treatment, physical changes happened on their surfaces as well as chemical changes which have been test using AFM technique. Three spectra are characterized by the appearance of halos extending in 2θ range from 16˚ to 45˚ for the XRD spectra of the untreated and treated Epoxy/Al composite samples at several exposed time (0, 2, and 4 min).